UNRAVELING THE TECHNICALITY OF TRANSLATING SHARI'A LEGAL TERMS IN LEGAL DISCOURSE FROM ARABIC INTO ENGLISH: ADEL SAQF AL-HAIT'S BOOK AS A CASE STUDY - Leena zaid alkeelani (جامعة النجاح الوطنية, 2025)
Legal translation is a difficult task to perform, especially between languages that are different from each other linguistically and culturally such as English and Arabic, since this leads to challenges faced by translators where this results in meaning distortion. Mahraj and Hdouch (2020) confirm this by saying that lexical items translated from an English legal discourse pose challenges to translators, since they may have different usage in the target language. As such, this study aimed at investigating the translation of Sharia legal terms from Arabic into English. It particularly concentrated on the translation of Sharia Legal Terms from Arabic into English in Dr. Azzam Adel Saqf Al-Hait's Book "The Reliable Guide to Legal Translation" to find out the translation strategies used by the translator in rendering these Sharia legal terms into English and the extent to which these strategies affected the meaning of these Sharia legal terms. In doing so, we concentrated on the translation strategies suggested by Vinay and Darbelnet (1995). In addition, we considered two more strategies that we felt important. These are the addition and omission translation strategies. We investigated 10 Sharia legal certificates translated into English, where we extracted examples from these certificates. Results indicated that the translator employed both oblique and direct translation strategies in his rendering of the Sharia legal terms under investigation. These are literal translation strategy, equivalence translation strategy, transposition translation strategy, modulation translation strategy, calque translation strategy, borrowing translation strategy. The translator used some of these strategies more frequently than the others. From direct translation strategies, the translator used literal translation strategy more than calque and borrowing. As for oblique translation, transposition, modulation and equivalence strategies were used more than the other strategies. Moreover, the translator also utilized omission and addition. We can mention that the translator depended a lot on the use of certain strategies especially literal translation, modulation, transposition and equivalence in his rendering of the Sharia legal terms into English, which had their impact on the meaning of the Sharia legal terms translated from Arabic into English. The translation led to full distortion, partial distortion and slight distortion as regards the meaning of the Sharia legal terms. Full distortion and partial distortion of the meaning were detected to occur more than slight distortion. We observed that literal translation strategy, omission strategy and equivalence strategy were the most problematic strategies for the meaning of the ST terms, where the omission and literal translation strategies are deemed the most problematic translation strategies, where equivalence strategy comes third. These strategies led to fully and partially distorting the meaning of the ST terms.
كشف الجوانب الفنية لترجمة المصطلحات القانونية الشرعية في الخطاب القانوني من العربية إلى الإنجليزية: كتاب عادل سقف الحيط كدراسة حالة